Sosialisasi Pemilu Damai dalam Memberikan Pemahaman Sikap Anti Politik Uang dan Anti Golput Bagi Pemuda Desa Pomah - Lati, Gustina Aruming Sekar; Saputro, Nur Ahmad; Jabbar, Abdul (Universitas Negeri Semarang, 2024)
Pomah Village is one of the villages located in Klaten Regency, Central Java, which is one of the locations held by UNNES GIAT 7. At this time, young voters have an important role in determining their voting rights for the political contestation process. However, not all young people understand and are aware of the importance of political education. Therefore, UNNES GIAT 7 students came up with the idea of a work program in the form of